Acute effects of dynamic stretching and self mobilization exercises on balance and proprioception - Akdağ, Mahmut Berat; Badilli, Feyza Şule; Akkuş, Zeki (University of Dicle, 2021)
The aim of this study was to investigate dynamic stretching applied to healthy individuals with tight hip flexor muscle and the effects of self-mobilization exercises on muscle tightness, balance and proprioception. 36 Participants with healthy hip flexor muscle tightness were included in the study. The participants with hip flexor muscle tightness were divided into two groups by simple randomization method. Measurement methods were applied before and after the exercise. Hipflexor muscle was measured by modified Thomas test. Proprioception was measured with digital inclinometer using the active knee extension method. Dynamic balance was measured by Y balance test. As a result of post-exercise evaluations in both groups, there was a significant improvement in muscle tightness after exercise (p=0.000). There was no significant difference in hipflexor muscle tightness between two groups (p=0.669). It was found no significant difference in all proprioception values except the 30 degree left extremity value in the dynamic stretching group (p=0.074). There was no difference between the groups in terms of proprioception (p=0.823).Dynamic balance results showed a significant increase in both groups (p =0.001). It was determined no significant difference between the groups in terms of balance. As a result, we can say that dynamic stretching and self-mobilization exercises can significantly improve muscle tightness and dynamic balance, do not significantly change proprioception. Thereis no difference between these two exercises in terms of these parameters.
Keywords: Dynamic Balance; Dynamic Stretching; Exercise; Muscle Tightness; Proprioception; Self-Mobilization